HASRAT TOKOH UTAMA DALAM NOVEL IKHTIAR CINTA DARI ADONARA KARYA J.S MAULANA (KAJIAN PSIKOANALISIS LACAN) - Darmadji, Regita Cahyani; Hinta, Ellyana; Masie, Sitti Rachmi (Pascasarjana, Universitas Negeri Gorontalo, 2021)
MAIN CHARACTER’S DESIRES IN IKHTIAR CINTA DARI ADONARA BY J.S MAULANA (A LACAN PSYCHOANALYTIC STUDY). RegitaCahyani Darmadji1, Ellyana Hinta2, SittiRachmi Masie3 Study Program of Indonesian Language and Literature EducationFaculty of Letters and Culture, UniversitasNegeriGorontalo *corresponding regitadarmadji1798@gmail.comUniversitas Negeri Gorontalo, ellyanahinta@ung.ac.idUniversitas Negeri Gorontalo, sittirachmi@ung.ac.id ABSTRACT The character in the novel is the main character with a desire created by the author. Basically, everyone will always feel desire. Thus, this study focused on the main character's desire in the novel Ikhtiar Cinta dari Adonara by J.S Maulana. This study aimed to describe the main character’s desires, including passive narcissistic, active narcissistic, active analytic, and passive analyticdesires. The descriptive analysis study employed Lacan's Psychoanalytic theory. The results of the study showed four character’s desires, in which the main character plays a direct role in forming the desires. Keywoards : the main character, desire, novel, Lacan psychoanalysis